Comparison of Cloud Computing and Grid Computing: A Review - Begum, S. Razool; Suganya, S (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing emerges as one of the hottest topic in field of information technology. Cloud computing is based on several other computing research areas such as HPC, virtualization, utility computing and grid computing. This topic discusses the grid and cloud computing in basics techniques. Typically, a grid works on various tasks within a network, but it is also capable of working on specialized applications. It is designed to solve problems that are too big for a supercomputer while maintaining the flexibility to process numerous smaller problems. Cloud computing is the delivery of computing services services–servers, storage, databases, networking, software, analytics, intelligence and more-over the Internet(“the cloud”) to offer faster innovation, flexible resources and economies of scale